Barium Sulfate Crystallization from Synthetic Seawater - Boon, Matthew; Jones, Franca (American Chemical Society, 2016)
Barium sulfate was crystallized in a synthetic seawater mixture that was chosen to better reflect ocean conditions. The synthetic seawater contained monovalent ions, magnesium, strontium, and calcium as well as bicarbonate and boric acid. The natural pH of the synthetic seawater is 8.1, and this seawater was used to determine the impact on morphology, nucleation rates, and incorporation of foreign ions. It was found that dendritic and diamond-shaped particles are both formed. The main parameters influencing the formation of dendritic particles were the saturation index and the ion ratio, but there was also a significant synergistic effect with the other ions present. The diamond-shaped particles formed later at a lower saturation index. The nucleation rate in synthetic seawater was found to be higher than expected based on an ion ratio basis. This is most probably because the divalent ions induce a higher nucleation rate by lowering the surface free energy. Strontium was found to be the dominant ion substituting for barium with some calcium substitution also occurring. Finally, the presence of silicate appeared to form dendritic particles with a larger aspect ratio and more impurities being present but little other impacts. The lack of change in the homogeneous nucleation rate supports a heterogeneous nucleation hypothesis.